Antioxidant and starch-hydrolyzing enzymes inhibitory properties of Striga-resistant yellow-orange maize hybrids - Elemosho, A.O.; Irondi, E.A.; Alamu, Emmanuel Oladeji; Ajani, E.O.; Menkir, A.; Maziya-Dixon, Busie (MDPI, 2021)
Most of the health benefits derived from cereals are attributed to their bioactive compounds. This study evaluated the levels of the bioactive compounds, and the antioxidant and starch-hydrolyzing enzymes inhibitory properties of six pipeline Striga-resistant yellow-orange maize hybrids (coded AS1828-1, 4, 6, 8, 9, 11) in vitro. The maize hybrids were grown at the International Institute of Tropical Agriculture (IITA), Nigeria. The bioactive compounds (total phenolics, tannins, flavonoids, and phytate) levels, antioxidant (DPPH• and ABTS•+ scavenging capacity and reducing power) and starch-hydrolyzing enzymes (α-amylase and α-glucosidase) inhibitory activities of the maize hybrids were determined by spectrophotometry. At the same time, carotenoids were quantified using a reverse-phase HPLC system. The ranges of the bioactive compounds were: 11.25–14.14 mg GAE/g (total phenolics), 3.62–4.67 mg QE/g (total flavonoids), 3.63–6.29 mg/g (tannins), 3.66–4.31% (phytate), 8.92–12.11 µg/g (total xanthophylls), 2.42–2.89 µg/g (total β-carotene), and 3.17–3.77 µg/g (total provitamin A carotenoids). Extracts of the maize hybrids scavenged DPPH• (SC50: 9.07–26.35 mg/mL) and ABTS•+ (2.65–7.68 TEAC mmol/g), reduced Fe3+ to Fe2+ (0.25 ± 0.64–0.43 ± 0.01 mg GAE/g), and inhibited α-amylase and α-glucosidase, with IC50 ranges of 26.28–52.55 mg/mL and 47.72–63.98 mg/mL, respectively. Among the six clones of the maize hybrids, AS1828-9 had the highest (p < 0.05) levels of tannins and phytate and the strongest antioxidant and starch-hydrolyzing enzymes inhibitory activities. Significant correlations were observed between total phenolics and the following: ABTS•+ (p < 0.01, r = 0.757), DPPH• SC50 (p < 0.01, r = −0.867), reducing power (p < 0.05, r = 0.633), α-amylase IC50 (p < 0.01, r = −0.836) and α-glucosidase IC50 (p < 0.05, r = −0.582). Hence, the Striga-resistant yellow-orange maize hybrids (especially AS1828-9) may be beneficial for alleviating oxidative stress and postprandial hyperglycemia.